Export mediated assembly of mycobacterial glycoproteins parallels eukaryotic pathways - VanderVen, Brian Chris, author; Belisle, John T., advisor; Gentry-Weeks, Claudia R., committee member; Inamine, Julia M., committee member; McNeil, Michael R., committee member; Reardon, Kenneth F., committee member (Colorado State University. Libraries, 2005)
Protein O-mannosylation is an essential and evolutionarily conserved posttranslational modification among eukaryotes. This form of protein modification is also described in Mycobacterium tuberculosis; however, the mechanism of mannoprotein assembly is fundamentally undefined. One M. tuberculosis H37Rv open reading frame (Rv1002c) was identified as a putative protein mannosyltransferase based on sequence similarities to known eukaryotic protein mannosyltransferases. To understand the initial stages of mycobacterial O-mannoprotein biosynthesis, Rv1002c was cloned and overexpressed in M. smegmatis. Cytoplasmic membrane extracts containing recombinant R vl002c enzymes were assayed for protein mannosyltransferase activity establishing that R vl002c functions as a protein mannosyltransferase. Two conserved amino acid residues of Rv 1002c that comprise a putative active site of eukaryotic protein mannosyltransferases are also required for R vl002c activity. Additionally, to determine what types of secreted proteins can potentially be mannosylated by M. tuberculosis a strategy utilizing differentially translocated chimeric proteins and mass spectrometry to monitor glycosylation was employed. Specifically, recombinant mycobacterial proteins secreted by the Sec (FbpC), SNM (ESAT-6) and SecA2 (SodA) pathways were fused to a native mycobacterial glycosylation domain from MPT32. These fusion proteins were expressed in mycobacterial hosts, purified, and analyzed for the presence of mannosylation. This approach established that M. tuberculosis protein mannosylation is dependent upon Sec-translocation and does not involve the SNM or SecA2 protein secretion pathways. Lastly, non-secreted forms of these fusion proteins and native cytosolic M. tuberculosis proteins were not mannosylated providing strong evidence that mycobacterial protein mannosylation occurs extracellularly.
Keywords: microbiology